Hacking Threat in Arab Cyberspace: How al-HaÌ„kirz al-MuslimuÌ„n Construct Narratives against Zionists and Anti-Islamists - Reflinaldi, Reflinaldi; Rahman, Bobbi Aidi; Rahmi, Awliya; Rezi, Melisa (Institut Agama Islam Negeri Curup, 2023)
The attack on the al-Aqsa mosque on April 6, 2023, and the burning of the Qur'an on January 21, 2023, have sparked a reaction from hacker group who call themselvesØ§Ù„Ù‡Ø§ÙƒØ±Ø² Ø§Ù„Ù…Ø³Ù„Ù…ÙˆÙ† Â (al-haÌ„kirz al-muslimuÌ„n) 'Muslim Hackers' (MH). Through the â€œHacker Newsâ€ YouTube channel, they threaten to hack several strategic and vital facilities of the Israeli and Swedish governments. About this phenomenon, this study aims to explain the construction of their threat narratives to those whom they call Zionists and anti-Islamists. Explanative qualitative research was conducted to answer research questions consisting of the formulation of themes, sequence of the scheme, and micro linguistic elements. Research data in the form of 2 videos of MH hacking threats were collected through manual transcription, reading and observation, printing, selection, and classification. Meanwhile, data analysis through the stages of reduction, presentation, analysis, interpretation, and conclusion was carried out by referring to Teun van Dijk's discourse structure model as an analytical framework. The results of the thematic structure analysis show that the theme highlights the actions as a response to attacks on Muslims and Islamic sacred symbols. MH asserts their identity as Muslims explicitly on the theme to attract the audience's attention. In line with these findings, the results of the schematic structure analysis show that the MH threat narrative scheme consists of the cause of threat, form of threat, detail of threat, and impact of threat. Microstructure analysis shows that MH uses clause structures, meaning intentions, and speech acts to launch psychological warfare against Zionists and anti-Islamists. Through this narrative, MH spreads fear with the target of putting political pressure on the Israeli and Swedish governments. Observing the increasingly massive and dynamic phenomenon of cyber warfare, it is predicted that MH's hacking threat narratives will often be found in conflicts and political dynamics in various countries.